Development of a TaqMan-based quantitative real-time PCR for the detection of Porcine circovirus type 3 - Hu, Zhiqiang; Lai, Ranran; Xu, Wei; Guan, Ran; Li, Mingxiang; Zhang, Zhimin; Hao, Guiying; Yan, Guangwen (Frontiers in Animal Science, 2025)
Porcine circovirus type 3 (PCV3) is a recently identified member of the porcine circovirus family, primarily associated with conditions such as dermatitis and nephropathy syndrome, reproductive failure, and multisystem inflammatory lesions in swine. There has been a significant increase in the prevalence of PCV3 in China, attracting considerable attention. Consequently, there is an urgent need for a highly sensitive, cost-effective, and efficient method for the detection of clinical samples. This study developed a TaqMan-based quantitative real-time PCR (TaqMan-qPCR) assay utilizing specific probes and primers designed based on the PCV3-REP gene. Following the optimization of reaction conditions, sensitivity analysis determined that the detection limit of this method was 7.3 × 100 copies/µL. Specificity analysis demonstrated no cross-reactivity with other common porcine pathogens, underscoring its specificity. Furthermore, the inter- and intra-assay coefficients of variation were both less than 1%, indicating high reproducibility. A total of 2,454 clinical samples were collected and analyzed using the developed method. The findings revealed that the prevalence of PCV3 was highest in testicular fluid samples, with a rate of 71.28% and the lowest detected Cq values among all sample types, indicating a significant likelihood of vertical transmission of PCV3. Additionally, oral fluid samples exhibited the second highest positive rate at 59.83%, highlighting the importance of monitoring infection rates in fattening pig herds from a veterinary perspective. In conclusion, this study successfully developed a highly sensitive and specific TaqMan-qPCR method, which is effective for detecting PCV3 across a variety of clinical samples.